The Limits of Meritocracy - Morgan, John (IMF Working Papers; Working Paper, 2018)
We show that too much meritocracy, modeled as accuracy of performance ranking in contests, can be a bad thing: in contests with homogeneous agents, it reduces output and is Pareto inefficient. In contests with sufficiently heterogeneous agents, discouragement and complacency effects further reduce the benefits of meritocracy. Perfect meritocracy may be optimal only for intermediate levels of heterogeneity.